English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

show me step to step answer

2006-11-07 17:26:10 · 16 answers · asked by Anonymous in Science & Mathematics Mathematics

16 answers

15+12(x-7)
15+12x-84
12x-69

2006-11-07 17:31:13 · answer #1 · answered by venomfx 4 · 0 0

Order of Operations
Parenthesis
Exponents
Multiplication
Division
Addition
Subtraction

3[5+4(x-7)]
Start with distributing the 4 to (x-7)
3[5+4x-28]
Combine like terms
3[4x-23]
Distribute the 3 to [4x-23]

=12x-69

2006-11-08 01:43:23 · answer #2 · answered by EmotionalStrength1022 2 · 0 0

3[5+4(x - 7)] do you remember PEMDAS?

please excuse my dear aunt sally which means do operations in this order:
parenthesis
exponents
mulitply
divide
add
subtract
if you do things in backwards order....wrong answer. so let's start

3[5 + 4(x - 7)] nothing to do in the parenthesis, but there are brackets so we start there. the 4 is. outside the parenthesis, so "distribute" multiply the 4:

3[5 + 4x -28] ok at this point you can do nothing with the 4x, but you can combine like terms by adding the +5 and -28 so:

3[4x -23] is what you will get. now distribute multiply the 3 thru the brakets:

12x - 69 there is your answer, hope this helped!!!! for more math help ask yahoo answers, or www.purplemath.com

2006-11-08 06:53:57 · answer #3 · answered by trish the dish 3 · 0 0

3[5+4(x-7)]
3[5+4x-28] Do what is in the parenthesis first.
3[4x-23] Next do what is inside the bracket.
12x-69 Next distriubte the 3 to the inside of the bracket.
12x-69 This is your answer.

Hope this helps.

2006-11-08 01:40:40 · answer #4 · answered by beaniejo_2004 3 · 0 0

3[5 + 4(x - 7)] = 0

3[5 + 4x - 28] = 0

3[ 4x - 23] = 0

12x - 69 = 0

12x - 69 + 69 = 0 + 69

12x = 69

12x/12 = 69/12

x = 5.75

The answer is x = 5.75

Insert the x value into the equation

- - - - - - - - - - - - - - - - - - - - - - - -

3[5 + 4(x - 7)] = 0

3[5 + 4(5.75 - 7)] = 0

3[5 + 4(- 1.25)] = 0

3[5 - 5]= 0

3 [ 0 ] = 0

0 = 0

- - - - - - - s-

2006-11-08 07:13:30 · answer #5 · answered by SAMUEL D 7 · 0 0

to factor or simplfy

3(5+4(x-7) distrub 4 over to x - 7 = 4x-28
3(5+4x-28) combine like terms so 5 - 28 = 23
3(4x-23) distrub 3 over to 4x - 23

12x-69

if you are solving for X it continue
12x = 69
12/12x = 69/12
x = 5.75 or 5 and 9/12

2006-11-08 04:41:14 · answer #6 · answered by hmongthaoboi 2 · 0 0

this is ur question
3[5+4(x-7)]

first u open the inside brakets
3[5+4x-28]

then u solve 5-28
3[4x-23]

then open the whole thing(multiply 3 and 4x - 3 and 23
12x-69

hope u got it...
take care
=D

2006-11-08 02:42:48 · answer #7 · answered by little_devil 2 · 0 0

3[5+4(x-7)] solve the inner bracket first
3[5+4x-28] solve the outer bracket
3[4x-23] solve the outer bracket after simplify
12x-69 solve

2006-11-08 03:01:50 · answer #8 · answered by safrodin 3 · 0 0

3[5+4(x-7)]
=3[5+4x-28]
=15+12x-84
=12x-69
start with the inner brackets and work your way out. (dont write that when you hand in your assignment. l.o.l).

2006-11-08 01:42:17 · answer #9 · answered by gerry zim 2 · 0 0

first start with innermost bracket

4(x-7)=4x-28

add this to 5

5+4x-28=4x-23

multiply this by 3 whixh ll give 12x-69

2006-11-08 01:32:20 · answer #10 · answered by aravind 3 · 0 0

fedest.com, questions and answers